Comparison of the Helsinki MoU 2005 and the Final Peace Agreement 1996: A Case Study of Aceh, Indonesia and Mindanao, Philippines - Mohammad Rafsanjani Akbar; Jamaluddin Jamaluddin (Genesis Law and Social Sciences, 2025)
Separatist conflicts in Southeast Asia, particularly in Aceh and Mindanao, have posed enduring challenges to national integration and regional peace. This study examines and compares the Helsinki Memorandum of Understanding (2005) and the Final Peace Agreement (1996) as frameworks for resolving these long-standing insurgencies in Indonesia and the Philippines. While both agreements aimed to establish autonomy and end armed conflict, their implementation and outcomes diverged significantly. Employing a qualitative comparative case study approach, the research analyzes legal texts, policy documents, and scholarly literature across five key dimensions: legal legitimacy, political participation, fiscal autonomy, security arrangements, and socio-economic impact. The findings indicate that the Helsinki MoU achieved more durable peace through comprehensive legal integration, inclusive governance, and stable fiscal mechanisms. In contrast, the FPA was hampered by weak institutional support, exclusion of critical stakeholders, and financial dependency, leading to continued unrest and eventual renegotiation. These results highlight the necessity of legally grounded, inclusive, and well-resourced agreements in achieving sustainable conflict resolution.